Effect of Manure Fertilizer Dosage and Mulch Types to The Vegetative and Generative Growth Performance of Cayenne Pepper Crops in Klungkung Regency, Bali - Retna Kumala Sari Anella (EDP Sciences, 2021)
Klungkung Regency is one of cayenne pepper centre producers in Bali. Mostly, cayenne pepper farming system in Klungkung Regency is done by applying traditional cultivation therefore cayenne pepper productivity in this regency still low. Agriculture technology dissemination such as the utilization of manure fertilizer is required to introduce to the farmers. The goal of this study was to understand the growth responses of cayenne pepper crop to the dosage of manure fertilizer application and mulch types. The research was conducted in July to December 2020 using Factorial Block Randomized Design with treatments were dosage of fertilizer manure namely 10ton/ha; 20 ton/ha; 30 ton/ha and mulch types namely straw and silver-on-black plastic mulch, replicated for 4 times. Parameters observed were plant height, stem diameter and branches amount during vegetative period and fruit weight, fruit length and fruit diameter during generative period. The results showed that interaction between dosage of manure fertilizer and mulch types significantly affected to overall parameters during vegetative and generative period except fruit diameter. Cayenne pepper growth was lower by application of 30 ton/ha of manure fertilizer compared to 10 ton/ha and 20 ton/ha. The utilization of silver black plastic mulch gives the better growth response than straw mulch.